Perancangan UI/UX Fitur Free Trial Pada Aplikasi Netflix Dengan Metode Design Thinking Proyek Kampus Merdeka Mitra PT. Zona Edukasi Nusantara (ZENIUS) - Kurniawan, Muhammad Aldino; Beny, Beny; Herty Yani (LPPM Universitas Dinamika Bangsa, 2024)
Netflix is an on-demand video streaming application which is very popular among the public. However, there are not a few new users who feel aggrieved by the policy of having to subscribe before being able to access the application. Therefore the author has the idea to design a User Interface and User Experience design for the free trial feature of the Netflix application. In this design the author uses the Design Thinking method which is widely used by UI/UX Designers to design an application. During the creation of the author assisted by the Mentor for the design and implementation. And as a result the author has succeeded in making a design plan which can then be implemented by Netflix.